2022
DOI: 10.3389/fonc.2022.942685
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-based planning for multi-isocenter VMAT total marrow irradiation

Abstract: PurposeTotal marrow irradiation (TMI) involves optimization of extremely large target volumes and requires extensive clinical experience and time for both treatment planning and delivery. Although volumetric modulated arc therapy (VMAT) achieves substantial reduction in treatment delivery time, planning process still presents a challenge due to use of multiple isocenters and multiple overlapping arcs. We developed and evaluated a knowledge-based planning (KBP) model for VMAT-TMI to address these clinical chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This notion has emphasized the importance of continued clinical efforts to improve the consistency and quality of radiotherapy planning using a variety of planning tools. [2][3][4][5][6][7][8][9] These include traditional knowledge-based planning tools that predict dosevolume histograms (DVHs), and deep learning-based tools, that predict dose distributions on computed tomography images for later DVH calculation. The more traditional knowledge-based planning tools typically use a library of plans from previously treated patients and develop models associating geometric features with their corresponding dosimetry to predict possibly achievable dosimetry for a new patient.…”
Section: Introductionmentioning
confidence: 99%
“…This notion has emphasized the importance of continued clinical efforts to improve the consistency and quality of radiotherapy planning using a variety of planning tools. [2][3][4][5][6][7][8][9] These include traditional knowledge-based planning tools that predict dosevolume histograms (DVHs), and deep learning-based tools, that predict dose distributions on computed tomography images for later DVH calculation. The more traditional knowledge-based planning tools typically use a library of plans from previously treated patients and develop models associating geometric features with their corresponding dosimetry to predict possibly achievable dosimetry for a new patient.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinics that utilize KBP demonstrated that KBP plans were non-inferior to manual planning and that planning time could be decreased. [13][14][15][16] To create high-quality plans using a KBP model, a database of "good" plans is required to train the model. Quality filtering is suggested to improve trained models.…”
Section: Introductionmentioning
confidence: 99%
“…These predictions can then be used to automatically generate optimization objectives, decreasing the amount of trial and error needed in manual treatment planning. Several clinics that utilize KBP demonstrated that KBP plans were non‐inferior to manual planning and that planning time could be decreased 13–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, multiple centers have developed and implemented intensity-modulated total body irradiation (IM-TBI), total marrow irradiation (IM-TMI) and total marrow and lymphoid irradiation (IM-TMLI) using modern linear accelerators (linac) and image-guidance [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Common to these techniques are the treatment of the patient in the supine position at the machine isocenter, volumetric imaging for image guidance, and inverse optimization within a treatment planning system (TPS).…”
Section: Introductionmentioning
confidence: 99%